2018
DOI: 10.1002/ece3.4768
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stability and assignment power of adaptively divergent genomic regions between herring (Clupea harengus) seasonal spawning aggregations

Abstract: Atlantic herring (Clupea harengus), a vital ecosystem component and target of the largest Northwest Atlantic pelagic fishery, undergo seasonal spawning migrations that result in elusive sympatric population structure. Herring spawn mostly in fall or spring, and genomic differentiation was recently detected between these groups. Here we used a subset of this differentiation, 66 single nucleotide polymorphisms (SNPs) to analyze the temporal dynamics of this local adaptation and the applicability of SNP subsets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…As both spawn timing and allele frequencies of collections from different spawning groups were stable over decades (electronic supplementary material, figure S3 and figure S4), genetic differentiation correlated with phenology appears to be a major determinant of population structure in Pacific herring. The interannual consistency of allele frequencies within a particular spawning population has also been observed in Atlantic herring [ 38 ], and demonstrates that populations exhibit seasonal and geographical fidelity to spawning sites across multiple generations. Our results support the hypothesis that Pacific herring home back to their natal spawning site.…”
Section: Resultsmentioning
confidence: 80%
“…As both spawn timing and allele frequencies of collections from different spawning groups were stable over decades (electronic supplementary material, figure S3 and figure S4), genetic differentiation correlated with phenology appears to be a major determinant of population structure in Pacific herring. The interannual consistency of allele frequencies within a particular spawning population has also been observed in Atlantic herring [ 38 ], and demonstrates that populations exhibit seasonal and geographical fidelity to spawning sites across multiple generations. Our results support the hypothesis that Pacific herring home back to their natal spawning site.…”
Section: Resultsmentioning
confidence: 80%
“…Discriminating autumn-and spring-spawning herring by applying genetic approaches is relatively new, but robust (Bekkevold et al, 2016;Martinez Barrio et al, 2016;Lamichhaney et al, 2017). In a recent study using 66 SNPs, Kerr et al (2019) could discriminate autumn and spring spawners with a 100% cross-validation accuracy and suggested that only six SNPs are needed to achieve such high accuracy. Further, Kerr et al (2019) also found a small number of heterozygous herring.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study using 66 SNPs, Kerr et al (2019) could discriminate autumn and spring spawners with a 100% cross-validation accuracy and suggested that only six SNPs are needed to achieve such high accuracy. Further, Kerr et al (2019) also found a small number of heterozygous herring. Increasing the number of SNPs in our study would increase accuracy to some extent but we have selected the loci that show the strongest association with spawning type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herring larvae used within this study were offspring from Baltic autumn spawners and laboratory-reared Atlantic/Baltic hybrid spring spawners. There are clear genetic differences between autumn and spring spawning herring (Martinez Barrio et al 2016, Lamichhaney et al 2017, Kerr et al 2019, but the mass-specific respiration rates and the effect of salinity were similar between the offspring of these two groups.…”
Section: Discussionmentioning
confidence: 99%